Konsili Yerusalem: Krisis Kesatuan Gereja dan Jalan Keluarnya - Prayidno, Iswadi (Institutum Ioannis Mariae Vianney Surabayanum, 2025)
The Jerusalem Council (Acts 15) stands as a pivotal moment in the early Church, revealing how the first Christian communities confronted internal conflict regarding the identity and boundaries of the emerging faith. This study examines the theological and cultural tensions between Jewish-Christian believers and the rapidly growing Gentile communities, which raised fundamental questions about salvation, the Mosaic Law, and ecclesial fellowship. By analyzing the deliberations involving Peter, James, Paul, Barnabas, and the Jerusalem elders, the paper highlights how discernment of God’s action—rather than adherence to inherited religious customs—guided the Council’s resolution. The resulting decision affirmed salvation by grace through faith and established minimal communal norms to enable fellowship between culturally diverse believers. The paper also reflects on the later disagreement between Paul and Barnabas as a reminder that human limitations do not negate God’s ability to work through conflict. Ultimately, the Jerusalem Council offers a lasting model for dialogue, discernment, and unity amid ecclesial diversity.